2017
DOI: 10.1093/biolre/iox123
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal immune activation depletes the ovarian follicle reserve and alters ovarian acute inflammatory mediators in neonatal rats†

Abstract: Normal ovarian development is crucial for female reproductive success and longevity. Interruptions to the delicate process of initial folliculogenesis may lead to ovarian dysfunction. We have previously demonstrated that an early life immune challenge in the rat, induced by administration of lipopolysaccharide (LPS) on postnatal day (PND) 3 and 5, depletes ovarian follicle reserve long term. Here, we hypothesized that this neonatal immune challenge leads to an increase in peripheral and ovarian inflammatory si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…Administration of LPS to neonatal rodents results in acute loss of primordial follicles Sominsky et al, 2015;Fuller et al, 2017), an observation duplicated in vitro using bovine ovarian cortex . During inflammatory processes activation of phosphoinositol 3 kinase (PI3K) results in conversion of phosphoinositol diphosphate to phosphoinositol triphosphate, with activation of protein kinase B (PKB, also known as AKT), which happens to be the pathway by which quiescent primordial follicles are activated to leave the resting pool and embark on development to ultimate atresia or ovulation .…”
Section: Inflammation Depletes the Pool Of Primordial Follicles (Ovarmentioning
confidence: 78%
See 1 more Smart Citation
“…Administration of LPS to neonatal rodents results in acute loss of primordial follicles Sominsky et al, 2015;Fuller et al, 2017), an observation duplicated in vitro using bovine ovarian cortex . During inflammatory processes activation of phosphoinositol 3 kinase (PI3K) results in conversion of phosphoinositol diphosphate to phosphoinositol triphosphate, with activation of protein kinase B (PKB, also known as AKT), which happens to be the pathway by which quiescent primordial follicles are activated to leave the resting pool and embark on development to ultimate atresia or ovulation .…”
Section: Inflammation Depletes the Pool Of Primordial Follicles (Ovarmentioning
confidence: 78%
“…The bidirectional communication between oocyte and cumulus cells is complex and not fully understood, but signaling molecules of the transforming growth factor (TGF)-β superfamily, particularly growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15, also known as GDF9b), are critical. Expression of BMP15 and of GDF9 in other organs is influenced by inflammation Fuller et al, 2017), and it is reasonable to assume that inflammatory processes in the ovary could affect the delicate interaction between oocyte and cumulus, with negative consequences.…”
Section: A Major Effect Of Uterine Disease Is Subsequent Failure Of Fmentioning
confidence: 99%
“…Previous studies showed that interleukins exert activities in the ovary, 41 neonatal immune activation depletes the ovarian follicle reserve, and accelerated follicle maturation alters ovarian acute inflammatory mediators. 42 Interestingly, our results revealed that the immune system process and regulation of cytokine production-related genes were induced in activated follicles, suggesting these factors might also play a role in the coordination of the primordial follicle to primary follicle transition. A similar finding was also reported by Kezele et al The authors identified 80 upregulated genes and 44 downregulated genes between the primordial and primary follicle stages using microarray gene chips in rats.…”
Section: Discussionmentioning
confidence: 67%
“…For morphometric analysis, 20 sections on 10 slides, 36 μm apart, were stained with haematoxylin-eosin (H&E). Two sections per slide were assessed on the basis of an 8 μm distance between the sections, allowing a complete assessment of primordial follicle counts at this location, as per our previous publications (42, 43). Follicles were classified as: (a) primordial : an oocyte surrounded by a single layer of flattened pregranulosa cells; (b) early primary : an oocyte surrounded by a single layer of flattened pregranulosa cells with at least two cuboidal granulosa cells; (c) primary : an oocyte surrounded by cuboidal granulosa cells; (d) preantral : follicles with no antral cavity and two or more layers of cuboidal granulosa cells; (e) antral : an antral cavity visible, with at least two layers of cuboidal granulosa cells.…”
Section: Methodsmentioning
confidence: 99%
“…Mean fluorescence intensity was calculated using a corrected total cell fluorescence (CTCF) formula (CTCF = integrated density—(area of selected section × mean fluorescence of background readings), as previously described (53). Data were normalized to the mean fluorescence intensity of the control group and expressed in arbitrary units (AU) (43, 54, 55).…”
Section: Methodsmentioning
confidence: 99%